Mission to Mars [videorecording (DVD)] - De Palma, Brian; Jacobson, Tom; Cannon, Lowell; Thomas, Jim (James E.); Thomas, John (Screenwriter); Yost, Graham; Robbins, Tim, 1958-; Sinise, Gary; Cheadle, Don; Nielsen, Connie, 1965-; O'Connell, Jerry, 1974-; Delaney, Kim; et al. (Touchstone Home Video, 2000)
NASA launches a Mars Recovery Mission to investigate and bring back survivors from the first manned mission to Mars which has mysteriously disappeared.